(untitled) (Bangladesh Journal of Botany, 2023)
To establish an efficient plant regeneration system of Cassia mimosoides, the 10-day-old seedlings were used as explants for inducing lateral buds. Results showed that the addition of BA and NAA for different ratios on the basis of 1/2 MS could effectively induce the production of lateral buds. By adding different additional elements, it was found that the growth of lateral buds was longer and stronger on the medium of 1/2 MS + 3.0 mg/l BA + 0.1 mg/l NAA + 4.0 mg/l Gln or 1/2 MS + 3.0 mg/l BA + 0.1 mg/l NAA + 1.0 mg/l AgNO3. Meanwhile, cutting with the lateral buds of tissue culture seedling, the rooting rate could reach 77.8% when 1/2 MS medium contained 0.2 mg/l NAA, although the root length was shorter. When the regenerated strong seedlings were transplanted into the soil, the survival rate was over 75%. Therefore, the best medium for lateral bud induction using 10-day-old seedlings as explants in C. mimosoides was 1/2 MS + 3.0 mg/l BA + 0.1 mg/l NAA. The growth of lateral buds can be promoted by the appropriate concentration of Gln and AgNO3, and the best rooting medium was 1/2 MS contained 0.2 mg/l NAA. Bangladesh J. Bot. 52(2): 515-521, 2023 (June) Special